2016
DOI: 10.1016/j.fm.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Vibrio parahaemolyticus and Vibrio vulnificus in various countries: A review

Abstract: Vibrio parahaemolyticus and Vibrio vulnificus are the leading causes of seafood associated infections and mortality in the United States. The main syndromes caused by these pathogens are gastroenteritis, wound infections, and septicemia. This article reviewed the antibiotic resistance profile of V. parahaemolyticus and V. vulnificus in the United States and other countries including Italy, Brazil, Philippines, Malaysia, Thailand, China, India, Iran, South Africa and Australia. The awareness of antimicrobial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
176
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(209 citation statements)
references
References 37 publications
11
176
0
4
Order By: Relevance
“…Our results revealed similar antibiotic susceptibility profiles in pandemic ST3, ST88, and non-pandemic isolates. This finding was similar to that in the work of Elmahdi et al (2016). They concluded that the sampling location or month in which the samples were collected did not significantly impact V. parahaemolyticus resistance patterns because isolates from both environmental and clinical sources shared similar antibiotic resistance profiles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results revealed similar antibiotic susceptibility profiles in pandemic ST3, ST88, and non-pandemic isolates. This finding was similar to that in the work of Elmahdi et al (2016). They concluded that the sampling location or month in which the samples were collected did not significantly impact V. parahaemolyticus resistance patterns because isolates from both environmental and clinical sources shared similar antibiotic resistance profiles.…”
Section: Discussionsupporting
confidence: 93%
“…They concluded that the sampling location or month in which the samples were collected did not significantly impact V. parahaemolyticus resistance patterns because isolates from both environmental and clinical sources shared similar antibiotic resistance profiles. Unsurprisingly, the majority of the isolates tested in this study showed ampicillin resistance, which is very common in V. parahaemolyticus isolates recovered from different sources (Sun et al, 2013; de Jesús Hernández-Díaz et al, 2015; Elmahdi et al, 2016; Mala et al, 2016). This result suggests that ampicillin should have a negligible role in the treatment of V. parahaemolyticus infection.…”
Section: Discussionmentioning
confidence: 74%
“…In the past, vibriosis was controlled (prevented or treated) almost exclusively through application of antibiotics or chemotherapeutic agents, either as feed additives or in immersion baths. However, extensive use of this approach over time has resulted in increased resistance of pathogenic Vibrio strains to the commonly used antibiotics: ampicillin, amikacin, kanamycin, penicillin G, streptomycin, and tetracycline (Austin and Austin 2007; Li et al 1999; Elmahdi et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In association with the rapid expansion of intensive mariculture and consequent deterioration of culture conditions, a steadily increasing number of Vibrio species are recognized as pathogens in vibriosis outbreaks (Austin and Zhang 2006; Cui et al 2014; Hou et al 2016). A limited number of antibiotics have been successfully applied, and resistance to these antibiotics may reduce the success of treatment programs (Al-Othrubi et al 2014; Elmahdi et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Seafood-associated infections is usually caused by V. cholera, V. parahaemolyticus and V. vulnificus (Raissy et al, 2012). Recent studies have shown that these species have become multidrug resistant (MDR) owing to the misuse of antibiotics in aquaculture production, and are thus major health threats to the public who become infected with seafood-borne diseases causes by antibiotic resistant Vibrio species (Elmahdi et al, 2016).…”
Section: Important Microorganisms In Antimicrobial Resistance Developmentioning
confidence: 99%